1997
DOI: 10.1007/bf02385776
|View full text |Cite
|
Sign up to set email alerts
|

The role of motilin and cisapride in the enteric nervous system of the lower esophageal sphincter in humans

Abstract: To assess the pharmacophysiological significance of the enteric nervous system and the responses of the human lower esophageal sphincter (LES) to motilin and cisapride, the mechanical responses of esophageal tissues from six patients with esophageal cancer and seven patients with gastric cancer were investigated. Circular muscle reactions were recorded to evaluate the in vitro esophageal responses to electrical field stimulation (EFS), motilin, and cisapride, evoking the adrenergic and cholinergic nerves befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
1
11
0
3
Order By: Relevance
“…In the gut, rat oesophagus muscularis mucosae contains smooth muscle 5-HT 4 receptors mediating relaxation (Baxter et al, 1991), an e ect suggested to be absent in the guinea-pig and dog (Cohen et al, 1994). In the human lower oesophageal sphincter, there is evidence for the presence of excitatory 5-HT 4 receptors on the cholinergic nerves (Tomita et al, 1997). In the gastric area, contractile 5-HT 4 receptors have been found on the cholinergic nerves in the guinea-pig (Buchheit & Buhl, 1994), dog (Bingham et al, 1995) and, based on preliminary data, man (Schuurkes et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In the gut, rat oesophagus muscularis mucosae contains smooth muscle 5-HT 4 receptors mediating relaxation (Baxter et al, 1991), an e ect suggested to be absent in the guinea-pig and dog (Cohen et al, 1994). In the human lower oesophageal sphincter, there is evidence for the presence of excitatory 5-HT 4 receptors on the cholinergic nerves (Tomita et al, 1997). In the gastric area, contractile 5-HT 4 receptors have been found on the cholinergic nerves in the guinea-pig (Buchheit & Buhl, 1994), dog (Bingham et al, 1995) and, based on preliminary data, man (Schuurkes et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…3 During the last decade, with the advent of improved techniques in such fields as pharmacology, electrophysiology, and immunohistochemistry, it has been suggested that the NANC nervous system, in addition to the two classical adrenergic and cholonergic components, may play an important role in the regulation of gastrointestinal motility. [4][5][6][7][8] However, the intramural innervation of the colon in patients with UC is not well understood. It seems reasonable to infer, therefore, that investigations of the NANC nervous system in the colon of patients with UC may help to clarify the pathophysiology of impaired colonic motility in this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Motilin, an endogenous prokinetic hormone, is secreted by gastrointestinal endocrine cells. Besides initiating gastric contraction that distally propagates in the gastrointestinal tract, motilin increases LES pressure acting both via the enteric nervous system and directly on the LES muscle (7). To the best of our knowledge, only a few studies evaluated the effect of H. pylori infection on motilin secretion.…”
Section: Introductionmentioning
confidence: 99%